Constituindo-se professor(a) : percursos, histórias e memórias docentes em Bento Gonçalves (1930-1960) - Scussel, Claudia Luci (My University, 2014)
This work discusses the history of teacher training based on the educational practices experienced by four teachers who worked in the municipality of Bento Gonçalves, state of Rio Grande do Sul, Brazil, when they were students in the decades of 1930 to 1960. It is based on Cultural History as its theoretical reference and authors such as Chartier, Foucault and Pesavento. In methodological terms the research project was guided by Oral History and made use of the writings of Halbwachs, Alberti, Ferreira and Amado. Through memories and autobiographical reports, the author investigates the relationship between the pedagogical experiences that the teachers had when they were students and their classroom practice as teachers. The narratives of life stories are seen as essential to understand the processes of schooling and the constitution of a professional identity and teaching practice that began when the teachers themselves were students. The author reconstructs the historical context of the ´1930s through the ´1960s. This period was characterized by educational practices based on nationalistic ideals, according to which discipline, progress and patriotism were the drivers towards a unified fatherland. The results show that, notwithstanding their different educational careers, the educational practices that the teachers experienced as students proved to be similar and influenced their attitudes in the classroom when they became teachers. Their representations of being a teacher expressed the losses they felt over time vis-à-vis their symbolic view of the teaching activity. The results include the central importance of discipline and respect for the teacher´s authority in the various pedagogical moments discussed here.
O presente trabalho estuda a história da formação docente a partir das práticas educativas vivenciadas por quatro professores(as) atuantes em sua carreira profissional no município de Bento Gonçalves(RS), enquanto alunos(as) das décadas de 1930 a 1960. Embasada no referencial teórico da História Cultural, utilizo Chartier, Foucault e as reflexões de Pesavento. A condução metodológica da pesquisa foi pautada na História Oral, tendo como referenciais Halbwachs, Alberti, Ferreira e Amado. Investigou-se, através de memórias e relatos autobiográficos, a relação existente entre as experiências pedagógicas vivenciadas na posição de alunos(as) e a sua prática em sala de aula enquanto professores(as). As narrativas de histórias de vida são consideradas essenciais para a compreensão dos processos de escolarização e da constituição de um ser/fazer docente que se inicia na condição de aluno(a). Este estudo trouxe presente o momento histórico dos anos de 1930 a 1960, pautados por práticas educativas alicerçadas nos ideais nacionalistas, os quais concebiam a ordem, a disciplina, o progresso e o civismo como os propulsores para uma Pátria unificada. Os resultados sinalizam que, apesar das distintas trajetórias de formação, as práticas educativas vivenciadas na posição de alunos(as) se mostraram semelhantes e influenciadoras das posturas assumidas em sala de aula, no momento em que se tornaram professores(as). Nas representações do ser professor(a) traduziu-se o sentimento de perdas que ocorreram com o passar do tempo com relação à visão simbólica da docência. Ficou evidenciada também a importância da disciplina e do respeito à autoridade do professor nos diferentes momentos pedagógicos, marca central desta pesquisa.
Keywords: Educação; Histórias de vida; História da formação docente; Representações da docência; Disciplina; Ensino - Bento Gonçalves (RS); Educação - Rio Grande do Sul; Life stories; History of teacher training; Representations of teaching; Discipline; Teaching - Bento Gonçalves (Brazil); Education - Rio Grande do Sul (Brazil)